Insurance Investment in Strategic Human Capital Development: The Pains and Gains from Panel Microdata - Akpan, Sunday S.; Nnamseh, Micheal P.; Mahat, Fauziah (Archives of Business Research, 2017)
This study examined the effect of insurance investment in strategic human capital development (SHCD) on performance of insurance companies in Nigeria. The fact that investment in SHCD is one of the most topical issues in the Nigerian insurance management and the continuous weak performance of insurance sector made this investigation necessary. The major objective of the study therefore was to examine the effect of insurance investment in staff training & development, wages & salary, retirement benefits compensation on employee value added (EVA), gross premium written (GPW), return on asset (ROA), and return on equity (ROE) of insurance companies. The study employed a quantitative research design and collected data from 20 insurance companies listed in Nigerian stock Exchange (NSE) over 2010 to 2014. The analysis was performed using pooled OLS, fixed effect and random effect estimation techniques. Results indicated that investment in SHCD on aggregate has no significant relationship with EVA but does with GPW, ROA and ROE whereas investment in SHCD practice like retirement benefits allowance has no relationship with all dimensions of performance of insurance companies. It was concluded that insurance investment in SHCD affect its performance unevenly. We recommend that management of insurance companies should train and develop its staff, devise incentivized salary and wags packages and committed to after work life benefits. This way, its SHCD investment will yield all-round proportionate increase in its performance in Nigeria.